應用福爾摩沙二號衛星遙測影像探討2008 年沃德‧亨特冰架崩解與裂隙、融池與浮冰時空變化之影響 - 張越程; Chang, Yueh-Cheng (2009)
冰架(ice shelf)不僅對氣候變相當敏感，其崩解(disintegration)也間接導致海平面上升與更嚴峻的暖化現象。一般而言，促使北極浮冰島(ice island)崩解(calve)的因素包含風的變化、海冰(sea ice)退卻、和冰架破裂(fracture)的擴張。雖然融池(melt pond)被視為冰架崩解的前兆，數量龐大的融池已經存在於部分加拿大極區冰架(Jeffries 2002)。但是這些融池和冰架崩解的關係至今仍未被完整的調查。本研究旨在利用高時空解析度影像為此提供初步的觀測和調查，以位於加拿大極區艾爾斯米爾島(Ellesmere Island)之沃德亨特冰架(Ward Hunt Ice Shelf)在2008 年三次的浮冰島崩解事件為例。此冰架自上個世紀初以來已經消失90%的面積，正說明了其對氣候變遷的敏感性。 國家太空中心(NSPO)於極區影像任務中在2007 年(2 幅)至2008 年(15 幅)夏季取得此冰架?多高時空解析度福爾摩沙二號衛星光學影像。融池、裂隙和浮冰等表面現象被萃取並用作變遷之分析。MODIS 影像也被用來分析第三次的崩解。 本研究有幾項發現。首先，融池的面積減少與裂隙長度的增加有高相關性。裂隙好發並擴張於融池以及溝豁(troughs) 間， 這顯示水力壓裂作用(hydro-fracturemechanism)對結構弱化的影響。此外，發展的趨勢意外的在七月十七日至二十八日間減少，顯示出有系統性的變化發生。其次，在2007 至2008 年夏季期間產生的溝豁發展成新的融池；部分並進一步成為裂隙(crevasse)以及崩解的冰緣(ice front)。這支持Holdsworth (1987) 有關此冰架丘豁交錯(hummocks and troughs)的獨特表面起伏特徵與海冰壓迫造成冰架彎曲的理論。這些現象不單為融水削弱冰架提出觀測上的證據，也符合水力壓裂作用在南極冰堡(ice berg)崩解中扮演的角色(Rist et al 2002;Scambos et al 2009a)。再者，此組影像也顯示海冰退卻與崩解的高相關性。最後，由入侵邊緣冰區的海冰流，延冰緣東向的海流，海冰在新的崩解灣(calving bay)的再次累積，以及冰架薄區域的分布等現象，可推測由迪斯雷利峽灣(Disraeli Fjord)經2002年發現的裂隙(crack)流出的季節性水流的存在，並證實其內淡水流失的現象(Jeffries etal 1990; Mueller et al 2003)。這海流可能也與差異化的冰架薄化(thinning 特別是底層融化)以及2002 年和2008 年發現的這些裂隙的產生有關。 這些發現暗示除了傳統的崩解因素(如冰架薄化、離岸風、海冰退卻、海浪傳遞)之外，底層海流與浮冰島及冰架崩解的間接相關性。除了更多資料的獲取與分析，這將會被用在未來對崩解的模型與模擬的研究中。 Ice shelves are vulnerable and sensitive to climate change Their collapses indirectly lead to sea-level rising and further climate change Typically speaking causes for ice island calving in the Arctic include change of wind sea ice retreat and fracture propagation Although melt pond has been regarded as a precursor of the collapse of ice shelves large numbers of melt ponds have been existed for at least a century in some of the ice shelves in the Canadian High Arctic (Jeffries 2002) But the relationship between melt pond and ice island calving has not been well investigated yet due to lack of proper tool This research aims to provide a preliminary insight in the relationship between ice-island calving and variations of features on the surface of ice shelf and sea from high spatiotemporal imagery The case study is the three calving events during 2008 melt season in Ward Hunt Ice Shelf (WHIS) Ellesmere in the Canadian High Arctic WHIS has lost 90% of its area since the beginning of the 20th century after its 3000+ years of existence which has been regarded as very sensitive but vulnerable to climate change In 2007 (2 scenes) and 2008 (15 scenes) high-spatiotemporal optical images of Formosat-2 were acquired successfully in Polar Image Campaign (PIC) by National Space Organization (NSPO) from June to August Surface features such as melt pond crevasse and sea ice are extracted from these images for spatiotemporal analysis MODIS imagery of WHIS is also employed to provide additional spatiotemporal information for the third calving event There are several findings Firstly the areal reduction of melt pond is highly correlated with the increase of crevasse length statistically Furthermore crevasse and rift tend to propagate through ponds and troughs implying the effect of weakening due to hydro-fracture mechanism However the trend slowed down during July 17th and 28th which reveals some systematical change in the drainage system Secondly new troughs are also observed during 2007-2008 winter and then became melt ponds; some of these further propagated as rifts and then resulted in calving developed into new ice front along with the ex-fracture in some area at last which supports Holdsworth’s propose (1987) related the formation of the unique land feature (with hummocks and troughs) to pack ice pressure plate buckling and creep formation as a result The above mentioned two phenomena altogether not only indicate that melt water does weaken the ice shelf but also align with the theories of hydro-fracture mechanism on ice-berg calving in the Antarctica (Rist et al 2002; Scambos et al 2009a) Thirdly this set of time-sequential imagery also shows that sea ice concentration over ice front has high correlation with calving events Lastly intrusive flow of pack ice to marginal ice zone eastward flow along the ice front and formation of new fast-ice near to the east of the new calving bay (18 August 2008) combined with the distribution of thin areas in the map of thickness altogether suggests that there is seasonal outflow from Disraeli Fiord through the central crack found in 2002 which is consistent to previous studies about the existence of the flow and the drainage of the freshwater (Jeffries et al 1990; Mueller et al 2003) The bottom flows probably contribute to differential thinning (especially bottom melting) and formation of cracks both found in 2002 and 2008 These findings imply that bottom flow is one of the potential mechanisms indirectly contributing to ice-island calving and ice-shelf disintegration in addition to traditional factors such as overall thinning off-shore wind sea ice retreat and wave propagation This is to be simulated in calving model furthermore in addition to refinement and verification with more field data and analyses